Extracorporeal Shock Waves Increase Markers of Cellular Proliferation in Bronchial Epithelium and in Primary Bronchial Fibroblasts of COPD Patients. (8th August 2020) - Di Stefano, Antonino; Frairia, Roberto; Ricciardolo, Fabio L. M.; Gnemmi, Isabella; Marino Gammazza, Antonella; Piraino, Alessio; Cappello, Francesco; Balbi, Bruno; Catalano, Maria Graziella
Abstract : Chronic obstructive pulmonary disease (COPD) is due to structural changes and narrowing of small airways and parenchymal destruction (loss of the alveolar attachment as a result of pulmonary emphysema), which all lead to airflow limitation. Extracorporeal shock waves (ESW) increase cell proliferation and differentiation of connective tissue fibroblasts. To date no studies are available on ESW treatment of human bronchial fibroblasts and epithelial cells from COPD and control subjects. We obtained primary bronchial fibroblasts from bronchial biopsies of 3 patients with mild/moderate COPD and 3 control smokers with normal lung function. 16HBE cells were also studied. Cells were treated with a piezoelectric shock wave generator at low energy (0.3 mJ/mm 2, 500 pulses). After treatment, viability was evaluated and cells were recultured and followed up for 4, 24, 48, and 72 h. Cell growth (WST-1 test) was assessed, and proliferation markers were analyzed by qRT-PCR in cell lysates and by ELISA tests in cell supernatants and cell lysates. After ESW treatment, we observed a significant increase of cell proliferation in all cell types. C-Kit (CD117) mRNA was significantly increased in 16HBE cells at 4 h. Protein levels were significantly increased for c-Kit (CD117) at 4 h in 16HBE (p < 0.0001) and at 24 h in COPD-fibroblasts (p = 0.037); for PCNA at 4 h in 16HBE (p = 0.046); for Thy1 (CD90) at 24 and 72 h in CS-fibroblasts (p = 0.031 and p = 0.041); for TGF β 1 at 72 h in CS-fibroblasts (p = 0.038); for procollagen-1 at 4 h in COPD-fibroblasts (p = 0.020); and for NF- κ B-p65 at 4 and 24 h in 16HBE (p = 0.015 and p = 0.0002). In the peripheral lung tissue of a representative COPD patient, alveolar type II epithelial cells (TTF‐1+) coexpressing c-Kit (CD117) and PCNA were occasionally observed. These data show an increase of cell proliferation induced by a low dosage of extracorporeal shock waves in 16HBE cells and primary bronchial fibroblasts of COPD and control smoking subjects.